Oral Preconditioning of Donors After Brain Death With Calcineurin Inhibitors vs. Inhibitors of Mammalian Target for Rapamycin in Pig Kidney Transplantation - Abbasi Dezfouli, Sepehr; Nikdad, Mohammadsadegh; Ghamarnejad, Omid; Khajeh, Elias; Arefidoust, Alireza; Mohammadi, Sara; Majlesara, Ali; Sabagh, Mohammadsadegh; Gharabaghi, Negin; Kentar, Modar; Younsi, Alexander; Eckert, Christoph; et al. (Frontiers in Immunology, 2020)
Background: The systemic inflammatory cascade triggered in donors after brain death enhances the ischemia-reperfusion injury after organ transplantation. Intravenous steroids are routinely used in the intensive care units for the donor preconditioning. Immunosuppressive medications could be potentially used for this purpose as well. Data regarding donor preconditioning with calcineurin inhibitors or inhibitors of mammalian target for Rapamycin is limited. The aim of this project is to investigate the effects of (oral) donor preconditioning with a calcineurin inhibitor (Cyclosporine) versus an inhibitor of mammalian target for Rapamycin (Everolimus) compared to the conventional administration of steroid in the setting of donation after brain death in porcine renal transplantation. Methods: Six hours after the induction of brain death, German landrace donor pigs (33.2±3.9 kg) were randomly preconditioned with either Cyclosporine (n=9) or Everolimus (n=9) administered via nasogastric tube with a repeated dose just before organ procurement. Control donors received intravenous Methylprednisolone (n=8). Kidneys were procured, cold-stored in Histidine-Tryptophane-Ketoglutarate solution at 4 °C and transplanted in nephrectomized recipients after a mean cold ischemia time of 18 hours. No post-transplant immunosuppression was given to avoid confounding bias. Blood samples were obtained at 4 hours post reperfusion and daily until postoperative day 5 for complete blood count, blood urea nitrogen, creatinine, and electrolytes. Graft protocol biopsies were performed 4 hours after reperfusion to assess early histological and immunohistochemical changes. Results: There was no difference in the hemodynamic parameters, hemoglobin/hematocrit and electrolytes between the groups. Serum blood urea nitrogen and creatinine peaked on postoperative day 1 in all groups and went back to the preoperative levels at the conclusion of the study on postoperative day 5. Histological assessment of the kidney grafts revealed no significant differences between the groups. TNF-α expression was significantly lower in the study groups compared with Methylprednisolone group (p = 0.01) Immunohistochemistry staining for cytochrome c showed no difference between the groups. Conclusion: Oral preconditioning with Cyclosporine or Everolimus is feasible in donation after brain death pig kidney transplantation and reduces the expression of TNF‐α. Future studies are needed to further delineate the role of oral donor preconditioning against ischemia-reperfusion injury.